EVALUASI KINERJA PELAYANAN ANGKUTAN UMUM BERUPA BUS BAGONG - Fandre (Universitas Islam Balitar Blitar, 2019)
The title of this thesis is “Performance Evaluation of Public Transport Service in the Form of Bagong Buses”. Bus is one of the public transportation that is needed by the community to support their activities. However, there are still many buses that operate in an unfit condition (age and condition of the vehicle). In addition, bus cleanliness also affects passenger comfort. In this study, researchers took the Bagong Bus sample. Data collection methods include questionnaires and documentation. Analysis of the data used is quantitative data. Data processing using SPSS version 20. The results obtained, the level of comfort (80.95%), cleanliness (94.44%), and service (66.67%) can be categorized quite well